Integrating Air Emission Inventory and Modeling and Evaluating Spread of Particulate Matter Caused by Rice Straw Open Burning in Hanoi City - Anh Le, Hoang; Quang Khoi, Ngo (VNU Journal of Science: Earth and Environmental Sciences, 2021)
Rice straw burning is an annual activity and a major contributor to local air pollution, concentrated in a short time in most agricultural countries like Vietnam. In this study, the air emission inventory tool is used to calculate the total amount of particulate matter (PM 10 , PM 2.5 ) generated from rice straw burning in the Winter - Spring crop in 2020 in Hanoi city. In the next step, the ADMS pollutant diffusion model was used to simulate the possibility of particulate matter transmission caused by the rice straw burning. The results show that with a total amount of 179.08 tons of PM 10 and 163.3 tons of PM 2.5 dispersed into the environment, causing local air pollution in the southern area of ​​the city, where there is a large cultivated area, the rice-yield is high and the amount of straw burned in the field accounts for the majority. To minimize the impact of rice straw burning activities, government and local authorities need to be more aggressive in implementing the directive to ban burning straw in the city and provide provide more practical alternatives to farmers.